Assessing integrated watershed management and spatial groundwater vulnerability to pollution in priority watersheds of the yacyreta dam in paraguay - Musálem Castillejos, K. (CATIE, Turrialba (Costa Rica), 2014)
Ilus. Tab. Bib.